Internal-external motor imagery and skilled motor actions - Fontani, G.; Migliorini, S.; Lodi, L.; de Martino, E.; Solidakis, N.; Corradeschi, F. (Journal of Imagery Research in Sport and Physical Activity, 2014)
The purpose of this study was to analyze the movement-related brain macropotentials (MRBMs) recorded during the execution of two tests of motor imagery: kinaesthetic (internal) and visual (external). Recordings were compared with those obtained performing a GO/NOGO motor test. The GO test required pressure of three keys of a modified keyboard in sequence when a figure appeared in the computer screen. On NOGO trials no button had to be pressed. Motor imagery tests were an internal or kinaesthetic imagination test (IN MI) on which participants imagined performing the pressure of keyboard buttons, avoiding any real movement, and an external or visual imagination test (EX MI) on which subjects were asked to imagine seeing their finger press the buttons. With the completion of the Movement Imagery Questionnaire, the participants were assigned into two groups: high (11) and low (10) capacity of imagination. The results showed an increase in the amplitude of the MRBMs wave occurring in the prestimulus period of imagination, with respect to real motor action. In the poststimulus period, the amplitude and duration of the waves recorded during motor action were higher than those recorded during the motor imagery tests. The comparison between EX and IN MI showed a lower latency and a higher amplitude of the brain waves recorded during internal motor imagery with respect to those observed during EX MI. The experimental data confirm that real motor activity is related to higher amplitude MRBMs than motor imagery. The profile of the waves recorded during internal imagery seems to be related to a higher brain involvement compared to those recorded during external visual imagery; it suggest that the kinaesthetic process of imagination is more efficient in information processing and motor skill acquisition.